(untitled) - Mara Alexandra Alves de Sousa; Soraia Cristina de Abreu Pereira; Armando Almeida; Liliana Andreia Neves da Mota; Fernanda Maria Príncipe Bastos Ferreira (Central European Journal of Nursing and Midwifery)
Aim: Advances in intensive care have reduced mortality rates but increased the number of survivors who face medium to long-term physical, cognitive, and psychological deficits. Nurses play a crucial role in aiding these individuals during their health transition process. The aim of this study was to examine the health consequences and nursing care needs of patients post-ICU. Design: Retrospective observational study. Methods: Data were collected between December 2017 and October 2020 through a retrospective analysis of 215 clinical processes. Descriptive and inferential statistical analyses were performed using SPSS, version 24. Results: While physical sequelae, such as respiratory and digestive issues, decrease over time, mental health issues persist. Quality of life, especially regarding mobility and daily activities, remains affected. Survivors face various self-care needs, including compromised ventilation, impaired swallowing, hallucinations, depressive mood, and anxiety, but also have potential for improving self-efficacy and daily task performance. Nursing interventions should focus on neuromuscular, gastrointestinal, psychological, and cardiorespiratory health. Conclusion: Survivors of critical illness experience significant changes that impact on their quality of life. Identifying their needs allows for more personalized nursing care and the development of a follow-up model that effectively addresses these challenges and highlights the benefits of nursing interventions on health outcomes.